Skill Measurement for Public Health Operations - พรหมมณี พัฒนา (Pathumthani University Academic Journal, 2019)
Skills were Expertise or ability to act or practice related to physical, intellectual or social abilities. They derived from training, accuracy, fluency. Expertise and durability and can be measured. Skills were divided into 6 levels as: 1) reflex movements, 2) basic-fundamental movements, 3) perceptual abilities, 4) physical abilities, 5) skilled movements, and 6) non-discursive communication The development of skill range consists of 7 steps as: 1) perception, 2) readiness, 3) guided response, 4) mechanism, 5) complex overt response, 6) adaptation, and 7) origination. Skills measurement was test of procedure or test item that meets purpose, time, environment, and met scope of practice, Skills can be measured with various measuring tools, including scale-estimation test, Check list test, and observation. The features of skills measurement tool are as follows: 1) validity, 2) reliability, 3) Discrimination, 4) objectivity, 5) difficulty, 6) efficiency, 7) searching, 8) fair, 9) definite, and 10) exemplary. All 10 measuring instruments were considered as excellent measuring instruments. In general, if it had only five qualifications as: 1) validity, 2) reliability, 3) discrimination, 4) difficulty, and 5) efficiency, it was a good quality measurement tool.